PERSPEKTIF TEORI WACANA VAN DIJK DALAM PIDATO PERDANA PRABOWO-GIBRAN USAI DITETAPKAN KPU JADI PEMENANG PILPPRES - Br Tarigan, Cindy Claren; Sapta Rindu Simanjuntak, Dairi; Simbolon, Ronaida; Harefa, Boisman; Pandiangan, Friska; Aritonan, Riwando; Elfrida Simatupang, Dina; Br Purba, Rika (Universitas Islam Sumatera Utara, 2024)
This research discusses the video broadcast of Prabowo-Gibran's first speech which was broadcast on the KompasTV YouTube media with the title